2019
DOI: 10.1002/jcb.29119
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HULC promotes lung squamous cell carcinoma by regulating PTPRO via NF‐κB

Abstract: Accumulating studies have implicated that long noncoding RNA (lncRNA) plays a vital role in lung cancer. However, little is known of the role of lncRNA highly upregulated in liver cancer (HULC) in the pathogenesis of lung squamous cell carcinoma (LSCC). In this study, we investigated the modifying effects and underlying mechanisms of lncRNA HULC in LSCC. Significantly decreased level of lncRNA HULC was observed in LSCC samples compared with adjacent tissues. Besides, the expression of lncRNA HULC was negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…They have been extensively studied in the carcinogenesis of many diseases, including cancer. Moreover, recent findings manifested that lncR-NAs are involved in a series of biological processes, such as cell proliferation, apoptosis, invasion and migration [9,10]. Furthermore, lncRNAs have been identified as new biomarkers of many malignancies, since they are associated with the complicated pathogenesis of malignancies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…They have been extensively studied in the carcinogenesis of many diseases, including cancer. Moreover, recent findings manifested that lncR-NAs are involved in a series of biological processes, such as cell proliferation, apoptosis, invasion and migration [9,10]. Furthermore, lncRNAs have been identified as new biomarkers of many malignancies, since they are associated with the complicated pathogenesis of malignancies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In lung squamous cell carcinoma, lncRNA HULC accelerates tumor progression by changing the expression of PTPRO through regulating nuclear factor-κB (NF-κB). 7 In breast cancer, lncRNA NONHSAT101069 regulates the miR-129-5p/ Twist1, promoting epirubicin resistance, migration, and invasion. 8 In osteosarcoma, lncRNA AFAP1-AS1 acts as an oncogene to promote the development and epithelialmesenchymal transition (EMT) via RhoC/ROCK1/ p38MAPK/Twist1 signaling axis.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [24] found that increasing the expression of the downregulated lncRNA LINC00961 resulted in increased Bax expression and the corresponding apoptotic death of NSCLC cells. Xu et al further provided evidence suggesting that the lncRNA HULC is able to promote LSCC cell proliferation owing to its ability to PTPROdependent phosphorylation and activation of NF-κB [25]. Similarly, Wang et al found that increased expression of the lncRNA MIR31HG in NSCLC led to enhanced tumor cell ge tinib resistance owing to associated activation of the EGFR/PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 98%